Effects of Brugmansia arborea (L.) Lagerheim (Solanacea) in the male reproductive system of mouse - Pino, José (2008)
The aim of this study was to investigate the effect of administration of aqueous extract of Brugmansia arborea (L.) Lagerheim-Angel’s Trumpet-on some reproductive parameters in mammals.Male mices were treated with 70 mg/kl/cw for 7 days, where they were euthanized and its testis, epididymis and its cauda region weights where determinate; so, the sperms number and its abnormalities were accounted. The testis and epididymis tail weight fell; sperm concentration was lower than control and the abnormalities rises. These results suggest that there is a negative effect of the dose of B. arborea than would alter the fertility of the mouse.